Regularity Of Cubic Graph With Application - Kishore Kumar Krishna; Hossein Rashmanlou; Ali Asghar Talebi; Farshid Mofidnakhaei (Journal of the Indonesian Mathematical Society, 2019)
A cubic graph is a generalized structure of a fuzzy graph that gives moreprecision, flexibility and compatibility to a system when compared with systems thatare designed using fuzzy graphs. In this paper, some properties of an edge regularcubic graph are given. Particularly, strongly regular, edge regular and bi-regularcubic graphs are defined and the necessary and sucient condition for a cubic graphto be strongly regular is studied. Likewise, we have introduced a partially edgeregular cubic graph and fully edge regular cubic graph with suitable illustrations.Finally, we gave an application of cubic digraph in travel time.